074 First seizures in emergency department vs ward: study in an elderly population. Issue 6 (24th May 2018) - Foster, Emma; Holper, Sarah; Kwan, Patrick
Abstract : Introduction: Seizures are common in hospitals, both as presentations to Emergency Departments (ED) and as hospital onset seizures (HOS), occurring in ward patients hospitalised for non-seizure reasons. Prompt identification of seizure aetiology is important, as it affects prognosis and management choices. Acute symptomatic seizures due to acute disturbance of brain function have a far lower risk of recurrence compared to unprovoked seizures. Timely investigations and specialist review assesses individual risk for seizure recurrence, which then guides therapeutic decisions including antiepileptic drug (AED) use. This study includes a larger proportion of older patients than usually reported, and as such, provides important insights into seizure aetiology and management strategies in this demographic. Methods: This retrospective survey of medical charts reviewed patients aged 18 or over with a hospital separation coded as ICD-10 G40 (Epilepsy), G41 (Status epilepticus), or R56.9 (convulsions not otherwise specified), presenting between 1 January 2008 through 30 November 2016, to a large metropolitan private hospital. 97 episodes of ED attendance for first seizure and 54 episodes of HOS were identified. Results: Median age was 70 years in ED-cohort and 80.5 years in HOS-cohort. Symptomatic seizure risk factors were identified in 62.89% of ED-cohort and 83.33% of HOS-cohort, including exposure to known epileptogenic drugs in 38.89% of HOS-cohort. Antiepileptic drugs (AEDs) were prescribed on discharge to 74.23% of ED-cohort and 81.48% of HOS-cohort, but far fewer had scheduled Neurologist review (58.76% of ED- and 35.19% of HOS-cohorts). Conclusion: This study includes a larger proportion of older patients than usually reported, and as such, provides important insights into seizure aetiology and management strategies in this demographic. This includes caution when prescribing known epileptogenic drugs; mindful prescription of AED on discharge; and ensuring adequate Neurologist follow-up to monitor further seizure activity, addressing seizure risk factors, and ongoing need for AED.